The Ambiguities of Academic Freedom - Marsden, George M. (Church history, 1993)
While most of the cases that led to the founding of the American Association of University Professors (AAUP) in 1915 had to do with firings of professors who had championed controversial political views, the AAUP founders were also concerned about dismissals on religious grounds. One case especially, that of Lafayette College, is particularly revealing not only of the character of the religious issues involved but also of the attitudes toward religion of those who defined what became the standard twentieth-century American concepts of academic freedom. Reflections on the religious dimensions of the construction of academic freedom in America also have important implications for religiously oriented higher education and scholarship today.